Competencies of a contemporary commander - Leslaw Welyczko; Robert Balcerzyk (Scientific Journal of the Military University of Land Forces, 2019)
The undermentioned considerations address a competent preparation of an officer for conducting tasks at his/her first duty assignment – a platoon leader. The article presents a peculiar triad of functions, i.e. a commander–a pedagogue–an instructor and roles to which every graduate of a military academy has to be prepared – to be capable of performing training-educational activities with subordinated soldiers. Only understanding of a magnitude of undertakings which are associated with preparation of best trained and educated officers of adequately shaped personality will allow a due addressing of the problem under consideration during developing of curricula in military academies.